Cat Kid comic club. On purpose - Pilkey, Dav, 1966- (New York : Graphix, 2022)
Trying to stay true to their vision as the comic club goes in all different directions, Naomi, Melvin and siblings search for their purpose until a desire for money and power clouds Naomi's judgment, which could mean the end for the club.
2.6
3-6.
GN310L
Keywords: Cats -- Comic books, strips, etc -- Juvenile fiction; Frogs -- Comic books, strips, etc -- Juvenile fiction; Clubs -- Comic books, strips, etc -- Juvenile fiction; Drawing -- Technique -- Comic books, strips, etc -- Juvenile fiction; Creative ability -- Comic books, strips, etc -- Juvenile fiction; Humorous stories; Cats -- Fiction; Frogs -- Fiction; Clubs -- Fiction; Drawing -- Technique -- Fiction; Creative ability -- Fiction; Humorous stories; Cartoons and comics; Humorous comics; Graphic novels; Comics (Graphic works)